Intravesicular Phosphatase PHOSPHO1 Function in Enamel Mineralization and Prism Formation - Pandya, Mirali; Rosene, Lauren; Farquharson, Colin; Millán, José L.; Diekwisch, Thomas G. H. (Frontiers in Physiology, 2017)
The transport of mineral ions from the enamel organ-associated blood vessels to the developing enamel crystals involves complex cargo packaging and carriage mechanisms across several cell layers, including the ameloblast layer and the stratum intermedium. Previous studies have established PHOSPHO1 as a matrix vesicle membrane-associated phosphatase that interacts with matrix vesicles molecules phosphoethanolamine and phosphocholine to initiate apatite crystal formation inside of matrix vesicles in bone. In the present study, we sought to determine the function of Phospho1 during amelogenesis. PHOSPHO1 protein localization during amelogenesis was verified using immunohistochemistry, with positive signals in the enamel layer, ameloblast Tomes’ processes, and in the walls of ameloblast secretory vesicles. These ameloblast secretory vesicle walls were also labeled for amelogenin and the exosomal protein marker HSP70 using immunohistochemistry. Furthermore, PHOSPHO1 presence in the enamel organ was confirmed by Western blot. Phospho1-/- mice lacked sharp incisal tips, featured a significant 25% increase in total enamel volume, and demonstrated a significant two-fold reduction in silver grain density of von Kossa stained ground sections indicative of reduced mineralization in the enamel layer when compared to wild-type mice (p<0.001). Scanning electron micrographs of Phospho1-/- mouse enamel revealed a loss of the prominent enamel prism “picket fence” structure, a loss of parallel crystal organization within prisms, and a 1.56-fold increase in enamel prism width (p < 0.0001). Finally, EDS elemental analysis demonstrated a significant decrease in phosphate incorporation in the enamel layer when compared to controls (p<0.05). Together, these data establish that the matrix vesicle membrane-associated phosphatase PHOSPHO1 is essential for physiological enamel mineralization. Our findings also suggest that intracellular ameloblast secretory vesicles have unexpected compositional similarities with the extracellular matrix vesicles of bone, dentin, and cementum in terms of vesicle membrane composition and intravesicular ion assembly.